Keratinized mucosa around implants in partially edentulous posterior mandible: 10‐year results of a prospective comparative study. Issue 4 (23rd February 2015) - Roccuzzo, Mario; Grasso, Giancarlo; Dalmasso, Paola
Abstract: Objective: The aim of this research was to investigate the clinical conditions around dental implants placed in the posterior mandible of healthy or moderately periodontally compromised patients, in relation to the presence or not of keratinized mucosa (KT). Materials and methods: One hundred and twenty‐eight patients who needed an implant in the posterior mandible were consecutively enrolled in a private specialist practice. Only one implant per patient was examined originally placed either within KT or alveolar (AM) mucosa. At 10 years, clinical and radiographic measures were recorded by a calibrated operator. The number of sites treated according to therapy modalities C and D (antibiotics and/or surgery) during the 10 years was also registered. Results: Ninety‐eight patients completed the 10‐year study. The absence of KT was associated with higher plaque accumulation, greater soft‐tissue recession (REC), and a higher number of sites that required additional surgical and/or antibiotic treatment. Patient‐reported outcomes regarding maintenance procedures presented major differences between the groups. In 11 of the 35 AM cases, additional free gingival graft (FGG) was successfully employed to reduce discomfort and to facilitate optimal plaque control. Conclusion: Implants that are not surrounded by KT are more prone to plaque accumulation and REC, even in patients exercising sufficient oral hygiene and receiving adequate supporting periodontal therapy (SPT). In selected cases, particularly in the edentulous posterior mandible, where ridge resorption leads to reduced vestibular depth and lack of KT, additional FGG can be beneficial to facilitate proper oral hygiene procedures.